Preparation method of high-heat-conductivity and high-density normal-temperature hydrogen storage material block
By mixing and pressing the normal temperature hydrogen storage material, binder and carbon material into a mass in proportion, combined with heat treatment technology, the low thermal conductivity and powderization problems of room temperature hydrogen storage alloy materials are solved, and a high thermal conductivity and high density hydrogen storage material block is achieved.
Patent Information
- Application Number
- CN202411982114.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The current thermal conductivity of hydrogen storage alloy materials at room temperature is low, resulting in low hydrogen absorption and desorption rates. It is easy to powder after circulating hydrogen absorption and discharge, making it difficult to meet the needs of fuel cells.
By mixing the normal temperature hydrogen storage material powder, binder powder and carbon material powder in a set proportion, pressing into a block, and heat treatment in a vacuum or inert atmosphere, the thermal conductivity and density of the material are improved.
It significantly improves the thermal conductivity of the material, reduces the contact thermal resistance of alloy particles, enhances the hydrogen absorption and release kinetic properties of the material, alleviates the material powdering phenomenon, and maintains a high hydrogen storage density.
Smart Images

Figure CN119703076A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen storage materials, and in particular to a method for preparing a high-thermal-conductivity and high-density room-temperature hydrogen storage material block. Background Art
[0002] Hydrogen is a promising energy carrier for sustainable development, with the advantages of being carbon-free, abundant in sources, and having a high mass-to-energy ratio. Hydrogen can be converted into electricity through fuel cells and used as a power source for vehicles and energy storage systems. Unfortunately, the lightweight and highly flammable nature of hydrogen poses a huge challenge to its storage. Typically, hydrogen is stored as a compressed gas in 35 MPa or 70 MPa Type IV hydrogen storage tanks for use in vehicles, or in stainless steel spherical hydrogen storage tanks at a pressure of 3-5 MPa for use in energy storage systems. However, the volumetric hydrogen storage density of compressed hydrogen storage tanks is low, and there are safety risks associated with hydrogen, making it challenging to promote its application in the automotive and energy storage fields. Therefore, finding efficient and safe hydrogen storage methods is crucial to promoting the development of the hydrogen energy industry chain.
[0003] Compared with gaseous hydrogen storage, solid-state hydrogen storage methods have lower energy consumption and are safer. Among a variety of solid-state hydrogen storage materials, titanium-based, rare earth-based, vanadium-based and other room-temperature hydrogen storage alloys have fast hydrogen absorption speed at room temperature and high volume hydrogen storage density, so they are considered to be one of the most promising solutions. Room-temperature hydrogen storage alloys must be filled into hydrogen storage tanks before they can be used. However, due to the low thermal conductivity of titanium-based, rare earth-based, vanadium-based and other room-temperature hydrogen storage alloy powders, the hydrogen absorption rate and desorption rate of the room-temperature hydrogen storage tank are significantly lower than the properties of the material itself, the thermal conductivity is low, and the heat released / absorbed during the absorption / desorption of hydrogen cannot be transferred in time, which in turn affects the hydrogen absorption and desorption performance of the device. In addition, the room-temperature hydrogen storage alloy will undergo pulverization after cyclic absorption and desorption of hydrogen, which is difficult to meet the needs of fuel cells. Therefore, it is necessary to improve the heat transfer characteristics of room-temperature hydrogen storage materials to increase the hydrogen absorption and desorption rate of room-temperature hydrogen storage materials.
[0004] Normally, the heat transfer performance of the material can be increased by the method of mixed pressing. However, the hardness of hydrogen storage alloy powder at room temperature is relatively large and it is not easy to press into sheets. By adding high thermal conductivity materials such as carbon, aluminum, and copper to the hydrogen storage material powder and pressing it into shape, a hydrogen storage material block can be formed, thereby improving the thermal conductivity of the material. Although the thermal conductivity of the hydrogen storage material can be improved by the mixed pressing method, the addition of a large amount of high thermal conductivity materials will significantly reduce the hydrogen storage density. Studies have found that after adding a binder to the hydrogen storage alloy powder and compacting it, although the thermal conductivity is increased and the hydrogen absorption and desorption kinetics of the material are improved, the hydrogen storage density is reduced.
[0005] Therefore, those skilled in the art are committed to developing a method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block, which greatly improves the thermal conductivity without affecting the hydrogen storage density. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to develop a method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block, which greatly improves the thermal conductivity without affecting the hydrogen storage density.
[0007] To achieve the above object, the present invention provides a method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block, comprising the following steps:
[0008] Step 1, mixing room temperature hydrogen storage material powder, binder powder, and carbon material powder uniformly according to a set mass ratio to form a mixture powder;
[0009] Step 2, putting the mixed powder into a tablet press mold and pressing it into a block;
[0010] Step 3, heat treating the block under vacuum or inert atmosphere;
[0011] Step 4: After the heat treatment is completed, cool it to the set temperature and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0012] In a preferred embodiment of the present invention, in step 1, the room temperature hydrogen storage material powder is one or more of titanium-based hydrogen storage material powder, rare earth-based hydrogen storage material powder, vanadium-based hydrogen storage material powder or high entropy hydrogen storage material powder, and the average particle size of the room temperature hydrogen storage material powder is not greater than 2 mm.
[0013] In a preferred embodiment of the present invention, in step 1, the binder is a thermoplastic material; preferably, the binder is any one of vinylidene fluoride PVDF or polytetrafluoroethylene PTFE.
[0014] In a preferred embodiment of the present invention, in step 1, the carbon material is one or more of spherical graphite, expanded graphite, carbon fiber or graphene.
[0015] In a preferred embodiment of the present invention, in step 1, the mass percentage of the room temperature hydrogen storage material powder is 95%-99%; preferably, the mass percentage of the room temperature hydrogen storage material powder is 96%, the mass percentage of the binder powder is 1%, and the mass percentage of the carbon material powder is 3%.
[0016] In a preferred embodiment of the present invention, in step 2, the compression molding pressure of the tablet press is 100-300 MPa, and preferably, the compression molding pressure of the tablet press is 150-220 MPa.
[0017] The tablet press type in the present invention can be selected from a single punch tablet press, a rotary tablet press or a hot press, etc.
[0018] In a preferred embodiment of the present invention, in step 2, the block is cylindrical, and the ratio of the diameter to the height of the cylindrical block is 1:0.05-2.
[0019] Preferably, the diameter of the cylindrical block is 10-12 mm and the height is 5-8 mm; or,
[0020] The cylindrical block has a diameter of 76-80 mm and a height of 10-35 mm; or,
[0021] The cylindrical block has a diameter of 93-97 mm and a height of 10-45 mm; or,
[0022] The cylindrical block has a diameter of 120-125 mm and a height of 15-50 mm; or
[0023] The diameter of the cylindrical block is 200-208 mm and the height is 25-70 mm.
[0024] In a preferred embodiment of the present invention, in step 3, the vacuum degree of the vacuum condition is not greater than 10 Pa, the heat treatment temperature is 0-150° C. higher than the melting point of the binder, and the heat treatment time is 0.1-1 hour.
[0025] Furthermore, when the binder is polyvinylidene fluoride, the heat treatment temperature is 300°C; when the binder is polytetrafluoroethylene, the heat treatment temperature is 350°C.
[0026] In a preferred embodiment of the present invention, in step 4, cooling is performed to 80° C. or below.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The present invention uses a pressing-cladding method to mix and press a binder with room-temperature hydrogen storage alloy powder, so that the binder and alloy particles are in close contact or embedded, and the binder is melted by heating, and the molten binder covers the alloy particles and adheres to the alloy particles, thereby reducing the contact thermal resistance of the alloy particles, so that the binder is coated on the room-temperature hydrogen storage alloy material particles, and a high thermal conductivity carbon material is filled between the hydrogen storage alloy material particles, thereby greatly improving the thermal conductivity of the material;
[0029] 2. The present invention partially covers the room temperature hydrogen storage alloy material after the adhesive such as polyvinylidene fluoride PVDF is melted, and the bonding force of the adhesive can resist the expansion stress of the alloy after hydrogenation, and slow down the breakage of the material caused by the stress of hydrogen absorption and desorption, so that the room temperature hydrogen storage alloy material can remain the same after multiple cycles of hydrogen absorption and desorption, and alleviate the material pulverization phenomenon;
[0030] 3. The present invention can realize large-scale room-temperature hydrogen storage alloy pressing by adding carbon materials and utilizing the lubricating effect of carbon materials such as graphite.
[0031] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the XRD diagram of the high thermal conductivity and high density room temperature hydrogen storage material block of Example 1;
[0033] Figure 2 The SEM and EDS images of the high thermal conductivity and high density room temperature hydrogen storage material block of Example 1;
[0034] Figure 3 This is a hydrogen absorption kinetics test curve of a high thermal conductivity and high density room temperature hydrogen storage material block in Example 1;
[0035] Figure 4 This is a hydrogen release kinetics test curve of a high thermal conductivity and high density room temperature hydrogen storage material block in Example 1;
[0036] Figure 5 This is the effective thermal conductivity curve of the high thermal conductivity and high density room temperature hydrogen storage material block in Example 1. DETAILED DESCRIPTION
[0037] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0038] In the drawings, components with the same structure are indicated by the same numerical reference numerals, and components with similar structures or functions are indicated by similar numerical reference numerals. The size and thickness of each component shown in the drawings are arbitrarily shown, and the present invention does not limit the size and thickness of each component. In order to make the illustration clearer, the thickness of the components is appropriately exaggerated in some places in the drawings.
[0039] Room-temperature hydrogen storage materials have the advantages of high volume hydrogen storage density, high safety, and simple hydrogen charging and discharging. They are important hydrogen storage materials in the fields of hydrogen energy storage and hydrogen transportation. The present invention develops a high thermal conductivity and high density room-temperature hydrogen storage material block and proposes a preparation method, which will provide a high-density, high thermal conductivity hydrogen storage material for the application of room-temperature solid-state hydrogen storage technology.
[0040] The following is an explanation through specific embodiments.
[0041] Example 1
[0042] A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block comprises the following steps:
[0043] 1: Mix TiMn2 (Zr, Fe, Cr) alloy powder with an average particle size of 1 mm, PVDF powder, and expanded graphite powder in a mass ratio of 96:1:3 to form a mixed powder;
[0044] 2: Put the mixed powder into the mold of the tablet press and press it into a block with a diameter of 10 mm and a height of 5 mm under a molding pressure of 150 MPa;
[0045] 3: Place the block in a furnace and treat it under 2Pa vacuum conditions and 300℃ heat treatment temperature for 0.5 hours;
[0046] 4: After the heat treatment is completed, cool it to 50°C and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0047] The XRD pattern of the prepared high thermal conductivity and high density room temperature hydrogen storage material block is as follows: Figure 1 As shown, SEM and EDS images are as follows Figure 2 shown.
[0048] Example 2
[0049] A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block comprises the following steps:
[0050] 1: TiMn2 (Zr, Fe, Cr) alloy powder with an average particle size of 0.3 mm, PVDF powder, and spherical graphite powder are mixed uniformly in a mass ratio of 97:0:3 to form a mixture powder;
[0051] 2: Put the mixed powder into the mold of the tablet press and press it into a block with a diameter of 10 mm and a height of 8 mm under a molding pressure of 180 MPa;
[0052] 3: Place the block in a furnace and heat treat it at 300°C in an Ar gas atmosphere for 1 hour;
[0053] 4: After the heat treatment is completed, cool it to 30°C and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0054] Example 3
[0055] A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block comprises the following steps:
[0056] 1: Mix TiMn2 (Zr, Fe, Cr) alloy powder with an average particle size of 0.85 mm, PVDF powder, and carbon fiber powder in a mass ratio of 95:1:4 to form a mixture powder;
[0057] 2: Put the mixed powder into the mold of the tablet press and press it into a block with a diameter of 10 mm and a height of 7 mm under a molding pressure of 160 MPa;
[0058] 3: Place the block in a furnace and treat it under 2 Pa vacuum conditions and 310 ° C heat treatment temperature for 0.1 hour;
[0059] 4: After the heat treatment is completed, cool it to 20°C and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0060] Example 4
[0061] A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block, comprising the following steps:
[0062] 1: LaNi5 alloy powder with an average particle size of 0.18 mm, PVDF powder, and expanded graphite powder are mixed uniformly in a mass ratio of 95:2:3 to form a mixed powder;
[0063] 2: Put the mixed powder into the mold of the tablet press and press it into a block with a diameter of 77 mm and a height of 20 mm under a molding pressure of 250 MPa;
[0064] 3: Place the block in a furnace and treat it under 10Pa vacuum conditions and 280℃ heat treatment temperature for 0.7 hours;
[0065] 4: After the heat treatment is completed, cool it to 50°C and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0066] Example 5
[0067] A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block comprises the following steps:
[0068] 1: LaNi5 alloy powder with an average particle size of 1.2 mm, PTFE powder, and graphene powder are uniformly mixed in a mass ratio of 96:1:3 to form a mixed powder;
[0069] 2: Put the mixed powder into the mold of the tablet press and press it into a block with a diameter of 95 mm and a height of 25 mm under a molding pressure of 100 MPa;
[0070] 3: Place the block in a furnace and heat treat it at 350°C for 0.3 hours under nitrogen atmosphere;
[0071] 4: After the heat treatment is completed, cool it to 80°C and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0072] Example 6
[0073] A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block comprises the following steps:
[0074] 1: V-Fe-Ti-Cr alloy powder with an average particle size of 2 mm, PVDF powder, and spherical graphite powder are uniformly mixed in a mass ratio of 96:1:3 to form a mixed powder;
[0075] 2: Put the mixed powder into the mold of the tablet press and press it into a block with a diameter of 122 mm and a height of 50 mm under a molding pressure of 300 MPa;
[0076] 3: Place the block in a furnace and treat it under vacuum conditions of <1 Pa and heat treatment temperature of 300 °C for 1 hour;
[0077] 4: After the heat treatment is completed, cool it to 20°C and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0078] Example 7
[0079] A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block comprises the following steps:
[0080] 1: Ti-Zr-V-Mn-Fe-Co high entropy alloy powder with an average particle size of 0.15 mm, PVDF powder, and expanded graphite powder are uniformly mixed in a mass ratio of 95:2:3 to form a mixture powder;
[0081] 2: Put the mixed powder into the mold of the tablet press and press it into a block with a diameter of 200 mm and a height of 60 mm under a molding pressure of 140 MPa;
[0082] 3: Place the block in a furnace and treat it under vacuum conditions of <1 Pa and heat treatment temperature of 300 °C for 1 hour;
[0083] 4: After the heat treatment is completed, cool it to 50°C and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0084] Example 8
[0085] A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block comprises the following steps:
[0086] 1: TiMn2 (Zr, Fe, Cr) titanium-based hydrogen storage alloy powder with an average particle size of 0.074 mm, PTFE powder, and spherical graphite powder are uniformly mixed in a mass ratio of 95:3:2 to form a mixture powder;
[0087] 2: Put the mixed powder into the mold of the tablet press and press it into a block with a diameter of 10 mm and a height of 5 mm under a molding pressure of 120 MPa;
[0088] 3: Place the block in a furnace and treat it at 6Pa vacuum and 400℃ heat treatment temperature for 0.4 hours;
[0089] 4: After the heat treatment is completed, cool it to 20°C and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
[0090] Experimental Example 1 Investigating the hydrogen absorption kinetics of the high thermal conductivity and high density room temperature hydrogen storage material block prepared in Example 1 of the present invention
[0091] The prepared high thermal conductivity and high density room temperature hydrogen storage material block was placed in a specific test sample rod, sealed, and connected to the PCT test equipment to test the hydrogen absorption kinetics of the material at 3MPa hydrogen pressure and 25°C. The test results are as follows Figure 3 As shown, the material can reach a hydrogen absorption capacity of 1.6 wt.% in 3.5 minutes.
[0092] Experimental Example 2: Hydrogen desorption kinetics of the high thermal conductivity and high density room temperature hydrogen storage material block prepared in Example 1 of the present invention
[0093] The prepared high thermal conductivity and high density room temperature hydrogen storage material block was placed in a specific test sample rod, sealed, and connected to the PCT test equipment to test the hydrogen desorption kinetics of the material at 0.15MPa hydrogen pressure and 5°C. The test results are as follows Figure 4 As shown, the material can achieve 1.4 wt.% hydrogen release in 3.5 minutes.
[0094] Experimental Example 3: The effective thermal conductivity of the high thermal conductivity and high density room temperature hydrogen storage material block prepared in Example 1 of the present invention is investigated.
[0095] The prepared high thermal conductivity and high density room temperature hydrogen storage material block is placed in a specific effective thermal conductivity test tank, sealed, and connected to a small solid-state hydrogen storage test system to test the thermal conductivity of the material under different hydrogen pressures, such as Figure 5 As shown. Figure 5 It can be seen that with the increase of hydrogen pressure, the effective thermal conductivity of the material and hydrogen mixed system also increases. When the hydrogen pressure is 3MPa, the effective thermal conductivity is 9.5W·m -1 ·K -1 .
[0096] The high thermal conductivity and high density room temperature hydrogen storage material block prepared by the present invention has the following industrial application prospects:
[0097] 1. Hydrogen-powered cars / bicycles / forklifts, etc.
[0098] Its efficient hydrogen storage characteristics can provide a stable energy supply for hydrogen fuel cell vehicles / bicycles / forklifts, etc., promoting the development of zero emissions.
[0099] 2. Fixed energy storage
[0100] Room temperature hydrogen storage alloy tablets have broad application potential in energy storage power stations and smart grids, and can effectively solve the problem of renewable energy volatility.
[0101] 3. Aerospace and defense
[0102] Due to its excellent performance and lightweight advantages, room temperature hydrogen storage alloy tablets have broad prospects in aerospace hydrogen storage equipment and military equipment.
[0103] 4. Small portable devices
[0104] Its high hydrogen storage density and safety make it suitable for portable hydrogen storage equipment such as field energy supply devices and portable hydrogen fuel cells.
[0105] In summary, room temperature hydrogen storage material blocks have shown broad prospects for industrial application with their excellent performance indicators and diverse application scenarios. With the rapid development of the hydrogen energy industry, continuous optimization of technology and reduction of costs, room temperature hydrogen storage material blocks will play a key role in energy structure transformation and sustainable development.
[0106] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block, characterized in that: The steps include: Step 1, mixing room temperature hydrogen storage material powder, binder powder, and carbon material powder uniformly according to a set mass ratio to form a mixture powder; Step 2, putting the mixed powder into a tablet press mold and pressing it into a block; Step 3, heat treating the block under vacuum or inert atmosphere; Step 4: After the heat treatment is completed, cool it to the set temperature and take it out to obtain a high thermal conductivity and high density room temperature hydrogen storage material block.
2. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 1, characterized in that: In step 1, the room temperature hydrogen storage material powder is one or more of titanium-based hydrogen storage material powder, rare earth-based hydrogen storage material powder, vanadium-based hydrogen storage material powder or high entropy hydrogen storage material powder, and the average particle size of the room temperature hydrogen storage material powder is not greater than 2 mm.
3. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 1, characterized in that: In step 1, the binder is a thermoplastic material; preferably, the binder is polyvinylidene fluoride PVDF or polytetrafluoroethylene PTFE.
4. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 1, characterized in that: In step 1, the carbon material is one or more of spherical graphite, expanded graphite, carbon fiber or graphene.
5. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 1, characterized in that: In step 1, the mass percentage of the room temperature hydrogen storage material powder is 95%-99%; preferably, the mass percentage of the room temperature hydrogen storage material powder is 96%, the mass percentage of the binder powder is 1%, and the mass percentage of the carbon material powder is 3%.
6. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 1, characterized in that: In step 2, the compression molding pressure of the tablet press is 100-300 MPa, and preferably, the compression molding pressure of the tablet press is 150-220 MPa.
7. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 1, characterized in that: In step 2, the block is cylindrical, and the ratio of the diameter to the height of the cylindrical block is 1:0.05-2.
8. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 1, characterized in that: In step 3, the vacuum degree of the vacuum condition is not greater than 10 Pa, the heat treatment temperature is 0-150° C. higher than the melting point of the binder, and the heat treatment time is 0.1-1 hour.
9. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 8, characterized in that: When the binder is polyvinylidene fluoride, the heat treatment temperature is 300°C; when the binder is polytetrafluoroethylene, the heat treatment temperature is 350°C.
10. The method for preparing a high thermal conductivity and high density room temperature hydrogen storage material block according to claim 1, characterized in that: In step 4, the temperature is cooled to 80° C. or below.
Citation Information
Patent Citations
Carbonic composite hydrogen storage alloy and preparation method thereof, composite solid hydrogen storage tank and hydrogen storage performance testing method
CN110788329A
Multi-plateau pressure type hydrogen storage device and manufacturing method of hydrogen storage sheet of multi-plateau pressure type hydrogen storage device
CN114046443A
High-thermal-conductivity and high-stability hydrogen storage alloy bed body for hydrogen storage tank and preparation process of high-thermal-conductivity and high-stability hydrogen storage alloy bed body
CN115650157A
Hydrogen storage alloy block material for filling solid hydrogen storage device and preparation method of hydrogen storage alloy block material
CN117430081A
Hydrogen storage alloy electrode and manufacture thereof
JP1992282559A
Cited By
Hydrogen storage material, preparation method thereof and hydrogen storage system
CN121085216A
Hydrogen storage material, method for producing the same, and hydrogen storage system
CN121085216B
Preparation method of metal hydride block, block obtained by preparation method and hydrogen storage equipment
CN121516818A
Anti-pulverization flame-retardant hydrogen storage composite material tablet as well as preparation method and application thereof
CN122301125A
Titanium-based hydrogen storage material, method for preparing the same and use thereof
CN122519986A